Mediation as a Form of Restorative Justice: Benefits of the Parties (Archives of Criminology, 2008)
The text discusses the positive aspects of the use of mediation as a form of justice. The author presents the characteristic features of the concept of restorative justice by outlining its typical features. The text also includes a comparative analysis of restorative and criminal justice and lists possible abuses resulting from the institutional appropriation of mediation. Janina Waluk stresses the two-sided benefits (for the perpetrator and the victim as well as for society and the administration of justice) stemming from the use of mediation, such as relieving the courts from cases considered to be minor, allowing the victim to ask questions of and forgive the perpetrator, to participate in solving their own case, and for the perpetrator to apologise, thus understanding what and to whom the harm was done, as well as restoring public trust in the administration of justice and the legal education of society. In conclusion, Waluk encourages the introduction of restorative justice conferences in local communities, which would aim to arouse interest in this solution among local authorities and local governments.